PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK PENINGKATAN KETERAMPILAN PROSES SAINS SISWA DALAM PEMBELAJARAN BIOLOGI DI KELAS XI SMA - Darmadi ' '; Yustina ' '; Shelly Maulise ' (Biogenesis, 2014)
This research aimed to determine the effect of Problem Based Learning model to theStudents' Science Process Skills of The Second Year Students of SMAN Plus of RiauProvince in learning Biology. This study was conducted from April to June 2013using the quasi experiment method with design research by posttest only controlgroup design. Samples were students of class XI.IA.4 (control class) and XI.IA.3(experimental class) which were determined based on random sampling technique.Research variables consisted of independent variables, namely Problem BasedLearning model and the dependent variable which was the students' science processskills with indicators were observation, communication, application, inference, andprediction. Data collected by using the observation sheet. The results showed that theobservation indicator on the control class was 66.67%, while the experimental class at100%. Communication indicator in the control class was 56.89%, whereas theexperimental class was 90.74%. Application indicator on the control class was33.33%, while 93.06% in the experimental class. Inference indicators on control classwas 39.56%, whereas the experimental class was 84.72%. Prediction indicator on thecontrol class was 33.33%, while the experimental class got 100%. The average scoreof process skills in control class was 45.96% with moderate category, while in theexperimental class was 93.70% with a very high category. Inferential statisticalanalysis results obtained t.test = 42.61> t.tabel 2.01 (significant). The students' highestskill score of science process skills were at observation and prediction skills (100%),while the lowest one was the inference skills (84.72%).Keywords: Learning Biology, Model Problem Based Learning, Science Process SkillsStudents